1990
DOI: 10.1093/jaoac/73.5.805
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Tri-Enzyme Extraction for Total Folate Determination in Foods

Abstract: A tri-enzyme digestion procedure using chicken pancreas conjugase, a-amylase, and Pronase® was evaluated to determine Its usefulness In the microbiological quantitation of total folate In foods. Folate values obtained by traditional conjugase digestion were compared to those obtained by the tri-enzyme method for 12 food products that represent diverse matrixes. The tri-enzyme treatment Increased measurable folate from most foods when compared to levels found after conjugase digestion. Largest Increases were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 0 publications
3
46
1
Order By: Relevance
“…Folate was extracted from the sample using a modification of the tri-enzyme extraction method. 11 Folate content was measured using the microplate adaptation of the microbiological assay at the University of Florida. 12 The folate content for the 100 bread samples was 202 Ϯ 94 g/100 g of bread (range 22-416 g/100 g).…”
Section: Folic Acid Content Of Breadmentioning
confidence: 99%
“…Folate was extracted from the sample using a modification of the tri-enzyme extraction method. 11 Folate content was measured using the microplate adaptation of the microbiological assay at the University of Florida. 12 The folate content for the 100 bread samples was 202 Ϯ 94 g/100 g of bread (range 22-416 g/100 g).…”
Section: Folic Acid Content Of Breadmentioning
confidence: 99%
“…The folacin values from a variety of commercially prepared shuttle menu items (Table 3) compared favorably with published data. Martin et al (1990) found 0.095 pg of folate/g (wet weight) of canned tuna; we found 0.084 -t 0.009 pg folate/g (wet weight) of the tuna-salad spread. In contrast, others have reported folate concentrations (per gram wet weight) of 0.11 l.tg/ g for yogurt, 0.1 I pg/g for smoked ham, and 0.49 pg/g for hardcooked eggs (Perloff and Butrum, 1977).…”
Section: Resultsmentioning
confidence: 39%
“…Although most foods analyzed were mixtures, mean folate values were similar to those reported by others for each primary vegetable. Martin et al (1990) found folate levels of 1.30 fig/g wet weight for frozen cauliflower and 1.26 pg/g for frozen spinach. In their review, Perloff and Butrum (1977) found folacin levels (per gram wet weight) of 0.56 pg in cooked broccoli and 0.44 pg in raw green beans.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The samples were loaded in an atomic absorption spectrophotometer to assess the concentration of iron. Likewise, fortified rice treatments were also scrutinized for folate concentration using trienzyme extraction following the protocol of Martin et al (1989). Purposely, 1 g rice sample was homogenized in 10 vol.…”
Section: Iron and Folic Acid Variations In Fortified Treatments Durinmentioning
confidence: 99%